Hagiographical motifs and visual identity: The late-medieval communal seal of Trogir - Marinković, Ana (Array, 2006)
The paper is based on iconographical analysis of the fifteenth-century communal seal from Trogir representing a fortified city featuring a bishop on its gates and a star above the towers. The generally-accepted textual model for this image is an episode from the second part of «Life of St. John of Trogir», written in 1203: in the year 1171 Venetian fleet attacked the city and on that occasion stole the hand relic of the Tragurian patron saint. St. John's Vita brings the account of the theft, of Tragurian requests and diplomatic actions to restitute the relic, which were followed by Venetian refusal, and the eventual miraculous return of the hand accompanied by a comet. In analysis of the genesis and significance of the visual motif, firstly it is discussed which were historical facts in the account of the theft, and the Venetians' motives for such an undertaking. Seventeenth-century historian Paulus Andreis, claims that the relic has been venerated in the church of St. John the Almsgiver (San Giovanni Elemosinario) on Rialto. Examination of Venetians' efforts to obtain a relic for this important church, as well as certain similarities between the cults of the two saints, suggests that the theft was programmed, and the relic of the Tragurian saint was meant to serve as surrogate for the relic of the church's actual patron saint. The second question is how does the Tragurian account correspond with furta sacra structures and motifs, and what significance does it bear for the local public. The tripartite model of passage rites, aplicable to the genre of furtive translationes, has been applied to the motifs which served as the basis for visual communal identity of Trogir. However, the model has shown here the inversed perspective: the final phase of aggregation is not represented through incorporation of the stolen relic as the patron saint of the new community, but through its return to the original community as the ultimate act of confirmation of the saint's patronage, maintained as the central motif of its official visual representation through the centuries. Finally, the moment of establishing of the episode, that is, the comet as the central motif that shaped communal identity of Trogir, is discussed. The image represented on the communal seal has been related in the literature to the hagiographical motifs of furtive translation and the relic's return in the seventeenth century by historian Johannes Lucius. However, already at the begining of the century, on the communal coat of arms placed on the bell-tower of the cathedral, the star is represented with the tail as the direct reference to the theft episode. Considering the fact that there is no trace of the star on the earlier communal seal of Trogir, it is suggested that the image was promoted only after the year 1420, with inauguration of Venice as the new Dalmatian ruler.